PERLINDUNGAN INDUSTRI DALAM NEGERI MELALUI TINDAKAN SAFEGUARD WORLD TRADE ORGANIZATION - Indraswari, A. A. Istri; Sudiarta, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
Protection of domestic industries through wto safeguards. safeguards are security measures undertaken by the government of the importing country to recover losses or to prevent serious threat of serious injury to the domestic industry-caused surge in imports of similar goods that directly compete. This research is normative because it examines the history of the law and the principle of legal principles and rules researching reviewing the written rules. safeguard arrangements refers to GATT article xix as enhanced safeguards agreement on 1994. security measures (safeguards) are also regulated in the Indonesian legal system by Presidential Decree number 84 of 2002 concerning the security measures of the domestic industry caused by imports rebound.
Keywords: Safeguard , Protection Of Industry, WTO